Pengembangan Media Informasi SMK Negeri 1 Plampang Berbasis Android - Widiya Lis Susana; Shinta Esabella; Atmawan Oktavia, Siska (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In the era of globalization and rapid technological development, schools as educational institutions must be able to adapt to these changes. One way to facilitate access to information about schools is by building a school Website that can be accessed by students, teachers, parents, and the general public. SMK Negeri 1 Plampang is one of the vocational high schools in Indonesia located in Sumbawa Regency, West Nusa Tenggara. The school has various programs such as Electrical Engineering, Welding Engineering, Ruminant Livestock Agribusiness, and others. As a school committed to providing the best education for its students, SMK Negeri 1 Plampang has built a school Website as one of the media to provide information about school activities, school profile, class schedules, student achievements, and others. However, school Websites that can only be accessed through a browser on a computer or laptop are sometimes less effective in providing access to information for students, teachers, and parents. Sometimes students or parents do not have access to a computer or laptop when needed, so the necessary information cannot be easily obtained. Therefore, the development of SMK Negeri 1 Plampang's Website into an android-based platform is a solution that is right to facilitate access to information for students, teachers, and parents. By developing SMK Negeri 1 Plampang's Website into an android-based platform, students, teachers, and parents can easily access school information through their smartphones. This android-based application will provide easy access to information, such as class schedules, assignments and exams, school profile, student achievements, and others. In addition, application users can obtain notifications about the latest information from the school, so they will not miss important information. In order to improve the effectiveness and efficiency of school information services, the development of SMK Negeri 1 Plampang's Website into an android-based platform is an appropriate alternative. With the android-based application, it is hoped that students, teachers, and parents can more easily obtain information about school activities, as well as have a better learning experience.